Rowing and pain: does rowing lead to exercise-induced hypoalgesia? - Tomschi, F.; Herzig, S.; Hilberg, T. (Applied Physiology, Nutrition, and Metabolism, 2024)
Physical activity acutely alters pain processing known as exercise-induced hypoalgesia (EIH). This randomized controlled crossover study investigated the effects of two different rowing exercises on EIH and to explore whether possible EIH effects are related to individual rowing specific performance. Fifty male experienced rowers conducted two rowing sessions (submaximal: 30 min of moderate rowing (70% of maximum heart rate); maximal: 350 m in an all-out fashion) and a control session. Pre and post exercise pain sensitivity was measured bilaterally using pressure pain thresholds (PPT; Newton (N)) at the elbow, knee, ankle, sternum, and forehead. Individual performance was determined as maximum watt/kg and was tested for correlations with changes in PPT. Higher PPT values were observed after maximal exercise at all landmarks with a mean change ranging from 2.5 ± 7.8 N (right elbow; p = 0.027; dz = 0.323) to 10.0 ± 12.2 N (left knee; p = 0.001; dz = 0.818). The submaximal (range from -1.6 ± 8.8 N (Sternum; p = 0.205; dz = 0.182) to 2.0 ± 10.3 N (right ankle; p = 0.176; dz = 0.194)) and control session (range from -0.5 ± 7.6 N (left elbow; p = 0.627; dz = 0.069) to 2.6 ± 9.1 N (right ankle; p = 0.054; dz = 0.279)) did not induce changes. Relative performance levels were not correlated to EIH (range from: r = -0.129 (p = 0.373) at sternum to r = 0.176 (p = 0.221) at left knee). EIH occurred globally after a short maximal rowing exercise while no effects occurred after rowing for 30 min at submaximal intensity. EIH cannot be explained by rowing specific performance levels in experienced rowers. However, the sample may lack sufficient heterogeneity in performance levels to draw final conclusions.